Sclerosing epithelioid fibrosarcoma: in‐depth review of a genetically heterogeneous tumor. Issue 8 (25th June 2021) - Murshed, Khaled A.; Al‐Bozom, Issam; Ammar, Adham
Abstract: First described in 1995 by Meis‐Kindbloom et al. as a variant of fibrosarcoma simulating carcinoma, sclerosing epithelioid fibrosarcoma (SEF) is a malignant soft tissue sarcoma characterized by epithelioid cells in dense sclerotic stroma, frequent immunoreactivity for MUC4 and heterogeneous genetic profile with recurrent EWSR1 gene rearrangement. It typically affects middle‐age adults with a predilection for the lower extremity. It is believed that SEF is closely related to low‐grade fibromyxoid sarcoma (LGFMS), both tumors show overlapping features in morphology, immunophenotype, and molecular profile. In this review, we discuss the clinical, morphologic, and immunohistochemical features of SEF with particular emphasis on its molecular diversity and relation to LGFMS.